Mediation Efficacy in Resolving Divorce Cases: A Case Study of the Purworejo Religious Court - Septi Indrawati; Riska Amelia (Journal of Judicial Review, 2023)
Marriage constitutes a sanctified event in the human experience, aimed at the establishment of a harmonious, serene, and comfortable domestic sphere. Within the Islamic framework, marriage is designed to forge a familial unit characterized by Sakinah, Mawadah, and Warahmah. This study endeavors to assess the efficacy of mediation in the resolution of divorce cases, ascertain the success rate of mediation within the Purworejo Religious Court, and identify the obstacles encountered by mediators in the implementation of Supreme Court Regulation Number 1 of 2016. Employing a normative-sociological approach, this research relies on legal inquiries utilizing both library resources and primary data gleaned directly from the community. The findings of this investigation reveal that Supreme Court Regulation Number 1 of 2016, serving as the legal framework for the management of divorce cases, has not effectively mitigated the escalating domestic conflicts. These conflicts stem from diverse factors, encompassing persistent disputes, abandonment, economic challenges, domestic violence, and various underlying issues, leading to a consistent increase in divorce cases over the years. Furthermore, the mediation process within the Purworejo Religious Court demonstrates a pronounced ineffectiveness, with a meager 9.95% success rate recorded between 2020 and September 2022. Consequently, all case studies involving the mediation process have proven unsuccessful in the resolution of divorce cases.